Analisis Pengaruh Karakteristik Dewan Pengawas Syariah Terhadap Perilaku Pengambilan Risiko dan Penghindaran Pajak Pada Perbankan Syariah Di Indonesia - Luciana Luthan; Ihsani Mazelfi (Akuntansi dan Manajemen, 2023)
Sharia Supervisory Board (DPS) in sharia banking plays an important role in supervising the activities of sharia banking to make sure that the bank can be free from usury (interest), gharar (unclear contract), and maisir (speculation). DPS in Islamic banks is expected to make Islamic banks more obedient to the rules. This study examines the effect of the DPS characteristics on risk-taking and tax avoidance behavior in Indonesian Islamic banking from 2010-2019. The characteristics studied included DPS financial expertise and the number of DPS meetings. Financial expertise is measured by the number of DPS who have expertise in finance. The research method used is multiple linear regression. The test results show that the number of DPS who are financial experts does not affect risk-taking behavior at Islamic banks. In contrast, the number of DPS meetings positively affects Islamic bank risk-taking. Then the number of DPS who are financial experts has a positive effect on tax avoidance at Islamic banks while the number of DPS meetings has no effect on tax avoidance at Islamic banks. The results of this study can be used as determinant to issue policies related to DPS responsibilities to maximize its role as a supervisory board in tax avoidance and risk taking.